Docking Assisted Prediction and Biological Evaluation of Sideritis L. Components with PTP1b Inhibitory Action and Probable Anti-Diabetic Properties - Eleftheriou, Phaedra; Therianou, Ekaterini; Lazari, Diamanto; Dirnali, Stavroula; Micha, Anna (Current Topics in Medicinal Chemistry, 2019)
Background: The main characteristic of Diabetes type II is the impaired activation of intracellular mechanisms triggered by the action of insulin. PTP1b is a Protein Tyrosine Phosphatase that dephosphorylates insulin receptor causing its desensitization. Since inhibition of PTP1b may prolong insulin receptor activity, PTP1b has become a drug target for the treatment of Diabetes II. Although a number of inhibitors have been synthesized during the last decades, the research still continues for the development of more effective and selective compounds. Moreover, several constituents of plants and edible algae with PTP1b inhibitory action have been found, adding this extra activity at the pallet of properties of the specific natural products. Objective: Sideritis L. (Lamiaceae) is a herbal plant growing around the Mediterranean sea which is included in the Mediterranean diet for centuries. The present study is the continuation of a previous work where the antioxidant and anti-inflammatory activities of the components of Sideritis L. were evaluated and aimed to investigate the potential of some sideritis’s components to act as PTP1b inhibitors, thus exhibiting the beneficial effect in the treatment of diabetes II. Methods: Docking analysis was done to predict PTP1b inhibitory action. Human recombinant PTP1b enzyme was used for the evaluation of the PTP1b inhibitory action, while inhibition of the human LAR and human T-cell PTP was tested for the estimation of the selectivity of the compounds. Conclusion: Docking analysis effectively predicted inhibition and mode of inhibitory action. According to the experimental results, four of the components exhibited PTP1b inhibitory action. The most active ones were acetoside, which acted as a competitive inhibitor, with an IC50 of 4 μM and lavandufolioside, which acted as an uncompetitive inhibitor, with an IC50 of 9.3 μM. All four compounds exhibited increased selectivity against PTP1b.
Keywords: Protein tyrosine phosphatase inhibitors